Fate and transport of free and conjugated estrogens during soil passage - Goeppert, Nadine; Dror, Ishai; Berkowitz, Brian (Environmental pollution (1987), 2015)
Endocrine disrupting chemicals, such as the free estrogens 17β-estradiol (E2), estrone (E1) and the conjugated estrogen estrone-sulfate (E1-3S) are found at low concentration levels in the environment. This is somehow contradictory to the strong sorption and high degradation potentials found in laboratory experiments. In particular, the fate and transport behavior of conjugated estrogens is poorly understood, and the importance of enzymes triggering the transformation pathways has received little attention. To address these deficiencies, the present research uses packed laboratory soil columns with pulse injections of free estrogens, either E2 or E1, or E1-3S, to provide sound evidence of the transformation pathways. It is further shown that (i) transport of free estrogens is subject to strong retardation and degradation, (ii) the transport of conjugated estrogens is less retarded and only to a minor degree affected by degradation, and (iii) arylsulfotransferase is the enzyme triggering the transformation reaction. [Display omitted] •The transformation pathway of E2, E1 and E1-3S is explained for Bet Dagan soil.•Arylsulfotransferase (ASULT) is the relevant enzyme operating in Bet Dagan soil.•E1-3S forms after E2 or E1 injection in Bet Dagan soil. The metabolic transformation pathway of E2, E1 and E1-3S in Bet Dagan soil has been clarified and the role of the enzyme arylsulfotransferase was identified.